The Impact of Scratch Programming on Improving Students English Skills - Yayang Ariawan; Djoko Sutrisno (Universitas Islam Negeri Palopo, 2025)
This study examines the influence of Scratch programming on enhancing students' proficiency in the English language. The research was carried out for a duration of two years in five primary schools. It employed a quantitative descriptive approach, gathering data using online surveys from a total of 18 instructors. The findings suggest that the use of Scratch programming has a substantial positive impact on different facets of English competence, such as the acquisition of vocabulary, comprehension of instructional material, reading and writing abilities, and grammar skills. Teachers expressed a strong understanding of Scratch and noticed significant enhancements in their pupils' linguistic skills. The results endorse the incorporation of visual programming languages such as Scratch into school curriculum as a means to successfully augment English language education. Additional research is advised to investigate the long-term effects and optimal methods for incorporating Scratch into language learning environments